Death and the Doctor (Existential Analysis: Journal of the Society for Existential Analysis, 2006)
Review of the academic literature and popular press suggests that physicians have considerable difficulty with issues of death and dying. This is often reductionistically attributed to such factors as insufficient training in communication skills, but death denial, death anxiety, and the emotion-management rules of the profession all play their part.